A descriptive study to assess the knowledge and expressed practices of primigravida mother’s regarding antenatal care and antenatal check-ups at selected government hospitals, Jodhpur, Rajasthan, India - Rai, Neha; Rathore, Jyoti (International Journal Of Community Medicine And Public Health, 2022)
Background: Pregnancy associated death remain high in developing countries. According to WHO, giving quality antenatal care will reduce pregnancy related diseases and deaths and thus protecting both antenatal mother and the baby. The world health organization reported that in 2015 around 830 women died every day from problems in pregnancy and childbirth. Only 5 lived in high-income countries. The rest lived in low-income countries. The WHO recommends that pregnant women should all receive four antenatal visits to spot and treat problems and give immunizations. Although antenatal care is important to improve the health of mother and baby, many women do not receive four visits. Methods: A quantitative approach, descriptive research design was used among 200 primigravida mothers coming to selected government hospitals, Jodhpur, Rajasthan, India by non-probability technique. Structured Questionnaire tools used to assess knowledge and expressed practices to assess antenatal care and antenatal check-ups. Data analysis was performed using Statistical Package for the Social Sciences version 20. Results: The study findings revealed that knowledge level of the primigravida mothers regarding antenatal care and antenatal check-ups out of 25 maximum score the mean knowledge score is 16.23. The expressed practices of the primigravida mothers regarding antenatal care and antenatal check-ups out of 17 maximum score the mean expressed practice score is 10.97. The study findings also revealed that significant association is present between sample characteristics and knowledge level. There is positive correlation (0.8121) found between knowledge and expressed practices. Conclusions: Knowledge and expressed practice regarding antenatal care and antenatal check-ups was average among primigravida mothers Umaid and MDM hospital, Jodhpur, Rajasthan.